Analisis Peluang Penghematan Konsumsi Energi Pada Kantor Pertanahan Kota Kendari - Hamisa, Hamisa Hamisa; Mangalla, Lukas Kano; Kadir, Abd (Teknik Mesin Universitas Halu Oleo, 2019)
In the modern era at this time, almost all human beings in all corners of the world have been dependent on the existence of electrical energy or it can be said that almost all the activities of a human being always have a relationship with electricity. This experimental study uses 2 methods of approach, namely initial energy audits and detailed energy audits. The tools used in this, the level of activity of Kendari City Land Office employees. The results of this study indicate that the initial energy audit at the Kendari City Land Office was 186, 9834 kWh / m2 (for 1 year), this has not exceeded the ASEAN-USAID standard on an office which is 240 kWh / m2 year while a detailed energy audit, the kWh value read at the Kendari City Land Office is 34.903,125 kWh (for 1 year). The opportunity to save energy (PHE) in energy audit research is to use lighting that is in accordance with its designation, perform cleaning on each AC unit which includes cleaning the air filter, fan blades, fins, evaporator and output grid on the AC. The recommendation for PHE is to do cleaning every 3-4 months for each AC unit and optimize the use of cloth curtains for each room at the Kendari City Land Office.Keywords : Initial Energy Audit, Detailed Energy Audit, Energy Consumption Intensity.